Circuitos curtos de comercialização (CCC): O caso das comunidades agroextrativistas da Amazônia paraense no norte do Brasil - BUENAVENTURA RAMÍREZ, Ivonne Maritza (2019)
This dissertation analyzes the difficulties and potentialities in the social construction of the short circuit markets, in the territory of the paraense Amazon, based on the case study of the Boa Vista community of Acará, located in the region of Lower Tocantins, near the city of Belém, capital of the state of Pará. This territory is characterized by presenting extensive areas of both land and forest and flooding forest bosqus, inhabited by agro-extractivist communities, mainly Afro-descendants, who have developed productive systems based on agroforestry systems or arrangements, where the cultivation of Cassava (Mandioca) and the integrated management of forest products provide resources for the production of products for self-consumption and commercialization. In this context, the forms of reproduction of these communities, made up of both agricultural and extractivist families, stand out for contributing to the sustainable development of the region, insofar as they preserve biodiversity, the protection of soils and water, while generating healthy foods. Having the characteristic of highlighting autonomy, represented in food security and sovereignty through the production of food for consumption. This study seeks to demonstrate that, even these communities that are characterized by having autonomy in their social reproduction, difficulties in fair market access, affect the permanence of families in these productive models, since financial needs motivate them to prioritize non-agricultural activities to generate income, and in some cases the rural exodus. In this context, the dissertation seeks to analyze to what extent the social construction of the markets via short marketing circuits, bringing together the producers of the consumers, through the exchange of information, knowledge and experiences, can contribute to the strengthening of these productive chains of biodiversity, supporting fairly in the generation of their income, as well as recognizing the important role of agro-extractivism for the sustainable development of the region. The conclusion is that the different forms of community organization, including associations and cooperatives, are strategic agents in the social construction of agroecological product markets, since they facilitate production, logistics and management processes, which in many cases it becomes complex to be developed at family level. It is also concluded that the accompaniment of extension or research entities or institutions is essential in the early stages of these processes. On the other hand, it is also concluded that the different forms of commercialization via short circuit, especially those related to producer organizations and responsible consumption groups, become strategic, avoiding the extensive bureaucratic procedures that are needed to access, for example, to the institutional market or government plans